Asset tracing and recovery - McQuillan, Alan (Henry Stewart Talks, 2009)
History of assets recovery, Al Capone, Meyer Lansky, Money laundering, Watergate, Key drivers of money laundering, Globalization of organized crime, Drug trafficking, New criminal business opportunities, Impact of money laundering, National political responses, International responses, Business model of organized crime, Strategic response, Terrorist groups, Toolkits of powers, Scale of the problem, The UK market, Asset seizures, Criminal attitudes, Knowledge gap, Ownership, Government, Border problems, Critical success factors
Archived at 2022/04/03